2021
DOI: 10.3390/mi12101185
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Fabrication of Novel Inkjet-Printed Silver Nanoparticle Sensors on Carbon Fiber Reinforced Nylon Composites

Abstract: Inkjet-printing technology enables the contactless deposition of functional materials such as conductive inks on surfaces, hence reducing contamination and the risk of substrate damage. In printed electronics, inkjet technology offers the significant advantage of controlling the volume of material deposited, and therefore the fine-tuning of the printed geometry, which is crucial for the performance of the final printed electronics. Inkjet printing of functional inks can be used to produce sensors to detect fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…[142][143][144] Karaş et al reported distinctive morphologies when a line with constant width was printed using different DS. [145] The printing generated arrays of individual drops when higher DS was used. The distance between drops, however, continued to decrease as DS decreased because more overlapping droplets were formed to fill the gaps in the pattern area (Figure 13a).…”
Section: Drop Spacingmentioning
confidence: 99%
See 2 more Smart Citations
“…[142][143][144] Karaş et al reported distinctive morphologies when a line with constant width was printed using different DS. [145] The printing generated arrays of individual drops when higher DS was used. The distance between drops, however, continued to decrease as DS decreased because more overlapping droplets were formed to fill the gaps in the pattern area (Figure 13a).…”
Section: Drop Spacingmentioning
confidence: 99%
“…Reproduced under the terms of the CC‐BY license. [ 145 ] Copyright 2021, Multidisciplinary Digital Publishing Institute; b) Graph of line width as a function of DS. Reproduced under the terms of the CC‐BY license.…”
Section: Printing Specificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, methods for strain measurement are also applicable for health monitoring. Strain gauges can be applied to the rotor surface [4][5][6] or between layers of carbon fibers. Since data transmission by slip rings is not practical at high speeds because of self-heating by friction [7], a telemetry system is required to record and transmit the data.…”
Section: Introductionmentioning
confidence: 99%
“…This article covered everything from ink formulation to product testing, showing how real inkjet printing products are developed. Karaş et al [ 15 ] made a strain gauge sensor on a carbon-fiber-reinforced polymer surface via direct inkjet printing. Their research focused on the excellent adhesion of inkjet-printed patterns and obtained good results.…”
mentioning
confidence: 99%